Health Insurance Status and Physician-Induced Demand for Medical Services in Germany: New Evidence from Combined District and Individual Level Data - Hendrik Jürges (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Germany is one of the few OECD countries with a two-tier system of statutory and primary private health insurance. Both types of insurance provide fee-for-service insurance, but chargeable fees for identical services are more than twice as large for privately insured patients than for statutorily insured patients. This price variation creates incentives to induce demand primarily among the privately insured. Using German SOEP 2002 data, I analyze the effects of insurance status and district (Kreis-) level physician density on the individual number of doctor visits. The paper has four main findings. First, I find no evidence that physician density is endogenous. Second, conditional on health, privately insured patients are less likely to contact a physician but more frequently visit a doctor following a first contact. Third, physician density has a significant positive effect on the decision to contact a physician and on the frequency of doctor visits of patients insured in the statutory health care system, whereas, fourth, physician density has no effect on privately insured patients' decisions to contact a physician but an even stronger positive effect on the frequency of doctor visits than the statutorily insured. These findings give indirect evidence for the hypothesis that physicians induce demand among privately insured patients but not among statutorily insured.
Keywords: I11; 330; supplier-induced demand; health care utilization; Gesundheitsversorgung; Nachfrage; Gesundheitswesen; Schätzung; Deutschland